UTILIZATION OF JKN DENTAL PROSTHETIC SERVICES AT FIRST LEVEL DENTAL HEALTH FACILITIES IN BALI - Lily, Gusti Ayu Yohanna; Siswomihardjo, Widowati; Hendrartini, Julita; Dipoyono, Haryo Mustiko; Wedagama, Dewa Made (Odonto : Dental Journal, 2021)
ABSTRACTBackground: The utilization of dental prosthesis services in Indonesia is rare, compared to other dental and oral health services. The use of prosthesis services in Bali is still relatively low compared to other parts of Western Indonesia. Based on data from BPJS Kesehatan Denpasar Branch Office, the demand for dental prostheses services by participants in the three working areas of BPJS Kesehatan Denpasar Branch Office is still low. Method: This research was conducted using quantitative research. The population were all participants providers of FKTP BPJS Kesehatan Badung Regency, and samples were taken through purposive sampling. Quantitative data were analyzed using binary logistic regression.Result: The results that the predisposing factors for JKN program participants (income, knowledge of dental prostheses, knowledge of JKN dental prosthesis services, perceptions of service quality, and perceptions of cost); enabling factor (access), and the need factor (the perception of pain when losing a tooth) contributions have a significant positive effect on the utilization rate of JKN dental prostheses. The predisposing factors (age and education) and enabling factor (social support) do not have a significant effect on the utilization rate of JKN dental prostheses. Conclusion: The results that the predisposing factors for JKN program participants contributions have a significant positive effect on the utilization rate of JKN dental prostheses.